Field notes contributed by Aaron Brees, fall 1996 - Brees, Aaronet al (1996)
List of birds and locations contributed by Aaron Brees. The field notes include a detailed description of the Pomarine Jaeger. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed